The influence of migration on women's use of different aspects of maternity care in the German health care system: Secondary analysis of a comparative prospective study with the Migrant Friendly Maternity Care Questionnaire (MFMCQ). Issue 1 (18th December 2019) - Seidel, Vera; Gürbüz, Burcu; Großkreutz, Claudia; Vortel, Martina; Borde, Theda; Rancourt, Rebecca C.; Stepan, Holger; Sauzet, Odile; Henrich, Wolfgang; David, Matthias
Abstract: Introduction: Approximately 21% of Germany's inhabitants or their parents have been born abroad. There is evidence that immigrant women are starting antenatal care later than nonimmigrants. In Berlin, equality in health care access had improved until 2011‐2012, leaving only women with Low German language proficiency and an insecure residence status particularly at risk. With the recent influx of refugees, we analyzed whether access to antenatal and postpartum care differs depending on immigration, residence status, income, and education. Methods: At our Berlin tertiary care center, a modified version of the Migrant Friendly Maternity Care Questionnaire was administered to women who delivered in the first half of 2017. Multivariate modeling compared nonimmigrant women, immigrants, and women who are direct descendants of immigrants. Results: The study included 184 nonimmigrant women, 214 immigrant women, and 62 direct descendants of immigrants. Germany is relatively good in prenatal care for immigrant women, as most are getting adequate prenatal care. However, 21% of immigrants compared with 11% of nonimmigrant women started pregnancy care after the first trimester ( P  = .03). Low income was a more powerful predictor than immigration status for starting prenatal care after the first trimester. Immigrant women (23%) were less informed on postpartum care availability than nonimmigrants (3%) and used less postpartum midwifery care. Conclusions: When designing health care interventions for immigrant women, not only migration‐specific factors should be considered but also low income as a barrier to access to maternity care.